Single pedicle superficial inferior epigastric artery flap versus bipedicle superficial inferior epigastric artery and superficial external pudendal artery flap: the flap perfusion and viability study in the rabbit model - Lye, Khoo Teng (2010)
Among the abdominal flaps, the superficial inferior epigastric artery (SIEA) flap is recognized as the least invasive technique with minimal donor site morbidity. It is usually raised as hemi-abdominal flap. The perfusion and viability of the SIEA flap extending above the umbilicus require further exploration with the rabbit paramedian SIEA flap model. The present study was undertaken to determine the vascular anatomy of the rabbit ventral abdomen, to develop a rabbit SIEA flap model and to compare the flap perfusion and viability between the single and bipedicle flaps. The vascular anatomy was dissected for direct observation and documentation. Twelve bilateral 12x5cm symmetrical paramedian flaps were raised on the ventral abdomen of six male New Zealand White rabbits. The right flaps were based single pedicle of SIEA whereas the left flaps were based on bipedicle of SIEA and superficial external pudendal artery (SEPA). The perfusion of flaps was objectively determined with laser Doppler flowmetry (LDF) and the flap viability was assessed with two-dimensional planimetry over 14-day duration postoperatively. The SIEA was the dominant vascular supply of the rabbit ventral abdomen. It was joined by the SEP A just proximal to the inguinal fat pad. There was no significant size muscular perforating vessel from the rectus abdominis or lateral abdominal muscles for establishing a perforator flap model. The LDF of the bipedicle SIEA/SEP A flap were marginally superior to single pedicle SIEA flap in overall mean (67.8±10.3 versus 59.2±10.3 perfusion units) and over time from postoperative day 1 to day 14 but the differences were not statistically significant (p>O.OS). The overall mean LDF reading at the centre of flap was higher than at distal flap (66.3±7.4 versus 60.7 ± 7.4 perfusion units) but the difference was not statistically different (p=0.561). The mean flap viability of the bipedicle SIEA/SEPA flap was better than the single pedicle SIEA flap (99.6± 6.6% versus 90.6±6.6%) but it was not statistically significant (p=0.361). The LDF measurements on post-operative day 1 and 3 moderately correlated with the outcome of flap viability on day 7 and 14 (p<O.OS). The paramedian rabbit SIEA flap model can be an analogue of the human SIEA hemi-abdominal flap that extends above the umbilicus. The single pedicle SIEA could achieve satisfactory perfusion and viability for both the ipsilateral vascular territories of the SIEA and lateral thoracic artery. There was no significant difference of flap perfusion and viability between single and bipedicle SIEA flaps .